Studies in Health Technology and Informatics Volume 8 - Open Systems in Medicine - Dombal, Tim De (IOS Press, 2014)
This book provides a snapshot describing intermediate results, steps for solutions and further directions of developments on the way to an integrated electronical medical record as a basis for complete fulfilment of all tasks in health care. It is obvious that an enterprise of such an extent has many cooperators and collaborations which cannot be completely cited. We wish to give our special thanks to all in the past and in the future who have helped in their individual context to bring about a functioning system, which will help for more rational access and handling to the problem of health care.